2020
DOI: 10.1002/mp.14355
|View full text |Cite
|
Sign up to set email alerts
|

A deep learning framework for prostate localization in cone beam CT‐guided radiotherapy

Abstract: Purpose: To develop a deep learning-based model for prostate planning target volume (PTV) localization on cone beam computed tomography (CBCT) to improve the workflow of CBCT-guided patient setup. Methods: A two-step task-based residual network (T 2 RN) is proposed to automatically identify inherent landmarks in prostate PTV. The input to the T 2 RN is the pretreatment CBCT images of the patient, and the output is the deep learning-identified landmarks in the PTV. To ensure robust PTV localization, the T 2 RN … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 52 publications
0
15
0
Order By: Relevance
“…The accuracy of the registration, and thus contour propagation, is adversely affected by image contents in one image that does not have correspondence in the other image, such as the presence/absence of bowel gas bladder filling on the CT images. 9 Besides, various image artifacts may ruin the global correspondence between pCT and CBCT. For example, metal artifacts may appear quite differently in different CT scans depending on the scanning modality and reconstruction algorithm.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The accuracy of the registration, and thus contour propagation, is adversely affected by image contents in one image that does not have correspondence in the other image, such as the presence/absence of bowel gas bladder filling on the CT images. 9 Besides, various image artifacts may ruin the global correspondence between pCT and CBCT. For example, metal artifacts may appear quite differently in different CT scans depending on the scanning modality and reconstruction algorithm.…”
Section: Introductionmentioning
confidence: 99%
“…For adaptive radiotherapy, an indispensable step toward the realization of this type of adaptive replanning is the segmentation of CBCT images. The accuracy of the registration, and thus contour propagation, is adversely affected by image contents in one image that does not have correspondence in the other image, such as the presence/absence of bowel gas bladder filling on the CT images 9 . Besides, various image artifacts may ruin the global correspondence between pCT and CBCT.…”
Section: Introductionmentioning
confidence: 99%
“…As compared with planning CT (PCT), the image quality of CBCT is relatively poor, such as low signal-to-noise ratio, motion, and fringe artifacts ( 11 , 12 ). The error of CT value between PCT and CBCT may be as large as 200 Hounsfield unit (HU) ( 13 , 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…Researches have demonstrated that increasing the delivered radiation dose to the breast cancer will improve the disease control, especially for the patients who suffer from the advanced disease. Image segmentation and localization technique will improve the quality of the treatment [1][2][3][4][5][6][7][8]. However, with the current tumor localization methods, increasing the delivered dose to the breast or the heart will result in a higher dose to the surrounding normal tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Different from the registration approaches based on the image intensity, in this paper, we establish a patient-specific deep learning model to achieve the breast auto-setup. The setup errors between the planning CT (pCT) and the daily CT is obtained by aligning the corresponding breast landmarks which are outputted from the deep learning model [8,[11][12][13]. It can address the drawbacks in the traditional methods through the following contributions: 1) Instead of requiring a large patient dataset, the training data in the article is generated using a patient-specific data augmentation strategy, which can account for the changes of the image content between the daily CT and the pCT.…”
Section: Introductionmentioning
confidence: 99%